การรับรู้สภาพปัญหาความเครียดของครูดนตรีในปัจจุบัน - กิ่งเงิน, ณัฐธิดา; อุทัยสุข, ดนีญา (An Online Journal of Education, 2018)
The objective of this research was to clarify the perception of the current stress problems of music teachers. The methodology used in this research was the Qualitative research method, consisted of descriptive interviews with music teachers. The key informants in this research were 30 music teachers, who has been teaching more than two years in both government school, private school in Bangkok. The research method consisted of reviewing literature of theories related to music teachers and the stress problems, developing the research materials, and using questionnaires to interview the music teachers. The results of the study identified six dimensions of problems, that music teachers encountered with. The problems can be classified into three main dimensions including misunderstanding of parents, time management, and teaching - related issues. The other three minor dimensions included stress from manager’s immorality management, financial issues, and social acceptance issues. The six problems found in this research could affect music teachers’ life quality in both health and working attitudes.